Testing the performance of macroinvertebrate metrics as indicators of changes in biodiversity after pasture conversion in patagonian mountain streams - Brand, Cecilia (2015)
Conversion of native forest to pastures is acommon practice worldwide; it has complex effects onriver biota that are related to activity type and intensity.This work was conducted in order to evaluate the effectsof cattle grazing on environmental features and to selectthe most appropriate measures based on the macroinvertebratecommunity as indicators of ecological changes.Physicochemical features, riparian ecosystem quality,habitat condition, and benthic macroinvertebrates wereinvestigated in streams draining pastures and were comparedto reference streams located in nonimpacted nativeforested catchments. Strong evidence of sediment depositionwas observed at pasture streams, which had higherpercentage of sand in the streambed but also increasedlevels of suspended solids. Pasture sites had significantlyhigher water temperature and conductivity as well aslower dissolved oxygen concentrations than did forestedsites. Both riparian quality and in-stream habitat conditionwere degraded at pasture sites. Among metrics, totalrichness, Ephemeroptera, Plecoptera, and Trichoptera(EPT) richness, Plecoptera richness, Shannon diversity,percentage of dominant taxon, percentage ofChironomidae species, shredder richness, and percentageof predator resulted to be the most consistent measures bydisplaying stronger responses to impairment. Our resultssuggest that forest conversion to pasture for livestockpractices is diminishing macroinvertebrate biodiversityand potentially changing functioning and dynamics ofPatagonian mountain streams as well. Damage preventionon riverine landscapes by restoring riparian ecosystems,replanting missing vegetation in buffer areas, andlimiting livestock access to the riverbanks could contributeto enhance the ecological integrity at converted areas.A more extended and comprehensive use of macroinvertebratemetrics could contribute to better understand andevaluate impact effects of these extended land use activitiesand to promote conservation strategies.